Collaborative Conceptual Change during Networked Management Learning - Dhariwal, Kewal (Proceedings of the International Conference on Networked Learning, 2008)
My research examines the collective construction of knowledge by participants as they complete problem-based exercises during collaborative supply chain simulations in competitive situations over the internet. My research has helped me to improve my educational practice with international students in my physical & virtual classrooms at various post-secondary institutions in Alberta, Canada. The business exercises and simulations (lesson plans & learning scripts) are co-constructions of a networked management learning (NML) activity/program with research participants, using a new technological innovation “ABiSim” a business simulator for use in the networked classroom. The business simulator while based on systems dynamics models enshrined in the ‘MIT Beer Game’ developed from ‘System Dynamics’ research (Forester, 1960), is an extensible, complex and dynamic system where decisions taken by individuals and strategies formed by groups can have far reaching outcomes. Iteratively evolving lesson plans and scripts provide for structured learning in a series of team-based competitive business games over the internet simulating real-time demand-driven integrated businesses, illustrative of emerging businesses alliances and management needs in international settings. Intelligent software agents provide for the exploration of “identities” which can be used to simulate different behaviours and assist managers to learn how to collaboratively construct new knowledge in emerging international business contexts. Research Contributions In carrying out my action research I am seeking to make a contribution to the theory and practice of personal inquiry which impacts and includes theory emerging from ‘the reflective practitioner’ (Schon, 1983); ‘living life as inquiry’ (Reason & Marshall, 1987), “living theory” (Levy, 2003) and ‘living educational theory’ (Whitehead, 2005) within networked management learning (Hodgson & Watling, 2004). My thesis is a personal inquiry where I ‘live life as inquiry’ using action research and personal engagement where I am both the researcher and subject and I use this approach to improve my own teaching practice (reflective practitioner) in the different teaching situations that I choose to engage with or in those that serendipitously find me. My focus is on me, my learning facilitation practice and the ICTs tools and techniques that I develop. I am interested in how I extract learning and new understanding through a critical analysis and examination of participant experiences during my courses, thereby contributing to living theory in adult, career, and technology education in networked arrangements - networked management learning. Collaborative Conceptual Change The subject matter in my courses focused on the management of information systems, integration both inter- and extra-enterprise, value chains and supply chain collaboration. Participant experiences in my version of NML and its design evolution are affected by how learners construct and make sense of what they experience, how they experience it and how they prefer to change their experience with flexibility to accommodate customized and personalized learning leading to greater engagement, group sense-making and deeper collaborative conceptual change. Outcomes of collaborative conceptual effort resulted in identification of participant understanding of business problems, problem formulation, learning engagement, personal and group motivation, team-construction, -building, -communications, -leadership, management, strategy formulation, planning, execution, issues related to transportation, inventory, costs, overhead, demand, supply, collaboration, trust, dependability, control, bullwhip, overloading, reactive systems, integrated information systems, enterprise resources planning, customer relationship management, service oriented architectures, and business process management. Initial course design had intended outcomes however unexpected outcomes emerged as a result of collaborative conceptual change in participants during various courses at different educational institutes.